2012
DOI: 10.2478/s11658-012-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of erythrocytes against oxidative and hypotonic stress by tannins isolated from sumac leaves (Rhus typhina L.) and grape seeds (Vitis vinifera L.)

Abstract: Erythrocytes are constantly exposed to ROS due to their function in the organism. High tension of oxygen, presence of hemoglobin iron and high concentration of polyunsaturated fatty acids in membrane make erythrocytes especially susceptible to oxidative stress. A comparison of the antioxidant activities of polyphenol-rich plant extracts containing hydrolysable tannins from sumac leaves (Rhus typhina L.) and condensed tannins from grape seeds (Vitis vinifera L.) showed that at the 5-50 µg/ml concentration range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…Recently, researches carried out by scientists of Bioorganic Chemistry of the Academy of Sciences of Uzbekistan, have shown prosperity of use of natural phenolic compounds as an antiviral, antioxidant, anti-tumor agents [14][15][16][17][18][19][20]. It was found that these compounds have high biological activity, which manifests itself in suppressing the activity of various viral infections, redox enzymes and etc.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researches carried out by scientists of Bioorganic Chemistry of the Academy of Sciences of Uzbekistan, have shown prosperity of use of natural phenolic compounds as an antiviral, antioxidant, anti-tumor agents [14][15][16][17][18][19][20]. It was found that these compounds have high biological activity, which manifests itself in suppressing the activity of various viral infections, redox enzymes and etc.…”
Section: Resultsmentioning
confidence: 99%
“…Alteration in membrane con ductance caused by tannin application can be one of the factors increasing the leakage current. In earlier studies of the effects of this tannin type on erythrocyte ghosts, relative hydrophobicity of tannin was reported [33]. Here we study effects of Rutan and its hydrolys able tannin on artificial membranes.…”
Section: Effects Of Tannin On Transmembrane Currents Inmentioning
confidence: 88%
“…There is speculation that this effect may be related to the presence of tannins in the Schinus terebinthifolius Raddi [48][49]. According to Olchowik and colleagues (2012) [50], the tannins are classified into two main groups, which structures are very different, although all of them have polyhydroxy phenols molecules or their derivatives. First group consists in hydrolysable tannins (such as tannic acid), commonly used for tanning leather and the second one contains other types of tannins, found in greater quantity and of greater importance in food, being called condensed tannins, which basic structure are related to the structure of catechin and 3', 4', 5, 7 -hydroxy-flavonoid [50].…”
Section: Discussionmentioning
confidence: 99%